Clinical Profile and Outcome of Asphyxiated Newborn in a Medical College Teaching Hospital - Panthee, Kiran; Sharma, Kiran; Kalakheti, Balkrishna; Thapa, Kul (Journal of Lumbini Medical College, 2017)
Introduction: Prenatal asphyxia, a major topic in neonatology, is a severe condition which has a high impact on neonatal mortality and morbidity and neurological and intellectual development of the infant. It is defined by WHO as "failure to initiate and sustain breathing at birth". It is estimated that around four million babies are born asphyxiated and among those one million die and an equal number of babies develop serious neurological consequences ranging from cerebral palsy and mental retardation to epilepsy. This study was done to identify the occurrence, clinical profile and, immediate outcome of prenatal asphyxia in Lumbini Medical College Teaching Hospital. Methods: It was a retrospective study where 82 cases that fulfilled the inclusion criteria were included between December 2014 to November 2015. Inclusion criteria included newborns with: a) APGAR score equal to or less than six at five minutes, b) requirement of more than one minute of positive pressure ventilation, c) signs of fetal distress (heart rate of less than 100 beats per minute, late decelerations). Results: Out of total 425 neonatal intensive care unit (NICU)admissions, 82 (19.3%) cases were of asphyxia among which 56 were inborn and 26 were referred from outside. Of those 82 cases, 47 (57.3%) cases developed hypoxic ischemic encephalopathy (HIE); HIE stage I had good outcome with survival rate of 95% and HIE stage III had poor outcome with survival rate of only 25%. Conclusion: Despite advances in management of neonates, prenatal asphyxia is still the leading cause of neonatal intensive care unit admission and mortality and morbidity in neonates. DOI: https://doi.org/10.22502/jlmc.v4i1.78 J. Lumbini. Med. Coll. Vol 4, No 1, Jan-June 2016, Page : 1-3